Progression and postoperative complications of osteoradionecrosis of the jaw: a 20-year retrospective study of 124 non-nasopharyngeal cancer cases and meta-analysis - Ziqin Kang; Tingting Jin; Xueer Li; Yuepeng Wang; Tianshu Xu; Yan Wang; Zixian Huang; Zhiquan Huang (BMC, 2022)
Abstract Background To assess the contributing risk factors for the progression of, and the postoperative poor prognosis associated with, osteoradionecrosis of jaw (ORNJ) following non-nasopharyngeal cancer treatment in head and neck. Methods A retrospective study of 124 non-nasopharyngeal carcinoma patients in head and neck treated at one institution between 2001 and 2020 was conducted. A cumulative meta-analysis was conducted according to PRISMA protocol and the electronic search was performed on the following search engines: PubMed, Embase, and Web of Science. After assessing surgery with jaw lesions as a risk factor for the occurrence of ORNJ, 124 cases were categorized into two groups according to the "BS" classification, after which jaw lesions, chemotherapy, flap reconstruction and onset time of ORNJ were analyzed through the chi-square test and t-test to demonstrate the potential association between them and the progression of ORNJ. Postoperative outcomes of wound healing, occlusal disorders, and nerve injury were statistically analyzed. Results With the statistically significant results of the meta-analysis (odds ratio = 3.07, 95% CI: 1.84-5.13, p < 0.0001), the chi-square test and t-test were used to validate our hypotheses and identified that surgery with jaw lesions could aggravate the progression and accelerate the appearance of ORNJ. Patients who underwent chemotherapy tended to suffer from severe-to-advanced osteonecrosis but did not shorten the onset time of ORNJ. Flap reconstruction presented obvious advantages in wound healing (p < 0.001) and disordered occlusion (p < 0.005). The mean onset time of ORNJ in non-nasopharyngeal cancer patients (4.5 years) was less than that in patients with nasopharyngeal cancer (NPC) (6.8 years). Conclusions Iatrogenic jaw lesions are evaluated as a significant risk factor in the occurrence and progression of ORNJ in non-nasopharyngeal carcinoma patients who tend to have more severe and earlier osteonecrosis after radiotherapy than NPC patients. Flap reconstruction is a better choice for protecting the remaining bone tissue and reducing postoperative complications of ORNJ.